Novel bioconjugation methods for protein microarrays and cell surface labelling - Hoop, Kelly Anne (University of Ottawa (Canada), 2010)
Chemical tools play an important role in research across many fields in science. The development of new tools for use in biology is therefore of the utmost importance. This thesis will discuss the development of two new chemically based tools for the field of biology. In the first part, the development of a new bioconjugation reaction will be discussed. The benzoin condensation was explored as a possible new bioconjugation reaction for the functionalization of surfaces with biomolecules. Using thiamine and other N-heterocyclic carbenes, it was shown that aromatic aldehydes can be tethered to a Si surface bearing a second aromatic aldehyde in aqueous media. In the second part, development of a new imaging technique will be discussed. Surface enhanced Raman scattering was successfully employed to image multiple targets on the surface of a cell. The design and synthesis of various Raman active ligand functionalized Ag nanoparticles allowed for the simultaneous imaging of two membrane proteins present in cardiomyocyte cells.
Keywords: Chemistry, Biochemistry.